Construction of ceRNA networks of lncRNA and miRNA associated with intramuscular fat deposition in Ujumqin sheep - Lan, Mingxi; Qin, Qing; Xie, Yuchun; Zhang, Chongyan; Liu, Zhichen; Xu, Xiaolong; Zhang, Jingwen; Xu, Songsong; Yang, Ji; Zhang, Haijun; Alatan, Suhe; Wang, Zhixin; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe molecular mechanisms underlying intramuscular fat (IMF) deposition are crucial for enhancing lamb meat quality. This process is regulated by a network of transcription factors. Exploring the role of non-coding RNAs, particularly lncRNAs and miRNAs, in IMF deposition can clarify its complex genetics and offer resources for breeding Inner Mongolian local breeds.MethodsWe evaluated carcass and lamb meat quality parameters using 60 six-month-old Ujumqin sheep with similar body weights. To investigate non-coding RNA’s role in IMF deposition, we identified differentially expressed genes and pathways between the longissimus dorsi and femoral biceps. Additionally, we analyzed these genes and the lncRNA-miRNA-mRNA co-regulatory network in high- and low-IMF femoral biceps groups.ResultsWe identified 11,529 mRNAs (747 differentially expressed), 9,874 lncRNAs (1,428 differentially expressed), and 761 miRNAs (12 differentially expressed). GO and KEGG enrichment analyses showed these genes are involved in lipid metabolism, fatty acid oxidation, and energy metabolism. We constructed a ceRNA network with 12 lncRNAs, 4 miRNAs, and 6 mRNAs. Notably, lncRNA MSTRG.13155.1 interacts with miR-1343-3p_R + 2, promoting IMF deposition by releasing HADHA gene expression. Dual-luciferase reporter assays confirmed MSTRG.13155.1 and HADHA as miR-1343-3p_R + 2 targets. RT-qPCR validated the expression trends of key mRNAs, miRNAs, and lncRNAs, consistent with sequencing results.DiscussionOur comprehensive analysis of differentially expressed genes and pathways in Ujumqin sheep’s longissimus dorsi and femoral biceps, along with high- and low-IMF groups, has revealed the complex genetics of IMF deposition. This offers valuable resources for Inner Mongolian local breed selection. The interaction between lncRNA MSTRG.13155.1 and miR-1343-3p_R + 2, and their regulation of HADHA expression, provides new insights into IMF deposition mechanisms. Future research can explore these mechanisms’ universality and specificity across different breeds and environments.